Using the knife to build the trust? The role of trust in the decision-making process of aesthetic surgeons and women patients/clients - Honelová, Michaela; Cook, Peta; Vidovićová, Lucie (Frontiers in Sociology, 2025)
Trust is a fundamental element in decision-making processes. In medicine, trust also helps to build relationships between patients/clients and doctors (aesthetic surgeons) and will influence a woman’s decision to undergo aesthetic/cosmetic surgery. Patients/clients, as well as aesthetic surgeons, use different ways to build trust. Our analyses are based on fifteen qualitative interviews with aesthetic surgeons, fifteen qualitative interviews with women who have undergone or are planning to undergo aesthetic surgery procedure(s) and non-participatory observations at the clinic of aesthetic surgery in the Czech Republic. Based on our analysis, three levels of trust were identified: macro level: trust in medicine as a social institution; meso level: a priori trust to the aesthetic surgeon; and micro level: trust in aesthetic surgeon and/or other medical staff in the process of medical aesthetic encounters. These results call for further studies outside of primary care and a deeper understanding of how these ‘voluntary’ medical specialties work and influence patients/clients and their ‘treatment’.